FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Anas Ismail; Triyono Triyono; Fathan Achyani (Universitas Muhammadiyah Surakarta, 2015)
This study analyzes the factors that affect the capital structure of a case study on property and real estate company that went public on the Stock Exchange 2008-2012. The aim of this study was to determine the optimal capital structure in a company. To measure it, the study uses five independent variables, namely the structure of assets, the company’s growth, company size, return on assets, and current ratio. The research sample using 37 property and real estate companies.This study uses egression analysis techniques. Results of this research is the size of the company and the current ratio significantly affect trade off theory according to which the company is more focused on profit, that profit is not reduced to pay installments external parties. Current ratio is a significant negative effect because the average property and real estate companies use more of its own models in comparison with debt